Dengue virus modulates critical cell cycle regulatory proteins in human megakaryocyte cells - Swarnendu Basak; Shovan Dutta; Supreet Khanal; Girish Neelakanta; Hameeda Sultana (Scientific Reports)
Abstract Suppression of human megakaryocytes by dengue virus (DENV) infection significantly reduces the platelet count that eventually leads to thrombocytopenia, severe dengue and death. To understand DENV interactions with megakaryocytes, we investigated the cell cycle in leukemic human megakaryocytic in vitro cell line (MEG-01 cells). Megakaryocytes are known for complex endomitotic cell cycle leading to their polyploidy state. Our study shows that DENV uses these polyploid cells for its replication. Understanding the modulation of DENV-mediated cell cycle regulation in megakaryocytes is therefore highly important. We show that DENV2 (serotype 2) infection significantly modulates cell cycle signaling. Our protein profile microarray data showed significant upregulation of several cell cycle regulatory proteins including CDK4, CDK1, Cyclin B1 and others or downregulation of Chk1, GSK3-beta, CUL-3, and E2F-3. Quantitative real-time PCR and immunoblotting analyses further confirmed the upregulation of CDK4, CDK1, and Cyclin B1 upon DENV2 infection. Gene silencing of CDK4, CDK1 and Cyclin B1 showed significant reduction in DENV2 loads. Immunoprecipitation analysis further revealed an enhanced interaction between Cyclin B1 and CDK1 upon DENV2 infection that perhaps suggest the substantial changes noted in cell cycle regulation. Overall, our study suggests that DENV2 modulates cell cycle signaling in megakaryocytes and interferes with the critical regulatory proteins that may eventually lead to changes in endomitosis process. In conclusion, we report an important molecular insight regarding DENV2-mediated cell cycle modulation in human megakaryocytes.